2017
DOI: 10.3847/1538-4365/aa937b
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Star Formation Histories on Stellar Mass Estimation: Implications from the Local Group Dwarf Galaxies

Abstract: Local Group (LG) galaxies have relatively accurate star formation histories (SFHs) and metallicity evolution derived from resolved color-magnitude diagram (CMD) modeling, and thus offer a unique opportunity to explore the efficacy of estimating stellar mass M of real galaxies based on the integrated stellar luminosities. Building on the SFHs and metallicity evolution of 40 LG dwarf galaxies, we carried out a comprehensive study of the influence of SFHs, metallicity evolution, and dust extinction on the UV-to-N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 130 publications
0
52
0
Order By: Relevance
“…The former method typically relies on some sort of theoretical or empirical underpinning relating observed quantities to physical properties, which can introduce some level of uncertainty. For example, uncertainties in galaxy star formation histories, stellar evolution tracks, obscuring dust geometries, and the initial mass function propagate to uncertainties in derived SFRs and stellar masses of observed galaxies (e.g., Maraston et al 2006;Conroy et al 2009;Michałowski et al 2010;Dunlop 2011;Walcher et al 2011;Conroy 2013;Leja et al 2017Leja et al , 2019Zhang et al 2017;Lower et al 2020). Similarly, uncertainties in spectral energy distribution (SED) modeling, or the conversion between emission-line strengths, continuum strengths, and gas masses are present in any measurement of the ISM properties of galaxies (e.g., Feldmann et al 2011;Narayanan et al 2011bCasey 2012;Bolatto et al 2013;Scoville et al 2014;Liang et al 2018;Privon et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The former method typically relies on some sort of theoretical or empirical underpinning relating observed quantities to physical properties, which can introduce some level of uncertainty. For example, uncertainties in galaxy star formation histories, stellar evolution tracks, obscuring dust geometries, and the initial mass function propagate to uncertainties in derived SFRs and stellar masses of observed galaxies (e.g., Maraston et al 2006;Conroy et al 2009;Michałowski et al 2010;Dunlop 2011;Walcher et al 2011;Conroy 2013;Leja et al 2017Leja et al , 2019Zhang et al 2017;Lower et al 2020). Similarly, uncertainties in spectral energy distribution (SED) modeling, or the conversion between emission-line strengths, continuum strengths, and gas masses are present in any measurement of the ISM properties of galaxies (e.g., Feldmann et al 2011;Narayanan et al 2011bCasey 2012;Bolatto et al 2013;Scoville et al 2014;Liang et al 2018;Privon et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Errors on colour/luminosity measurements are propagated separately. For the mass range of most galaxies in PROBES, the Roediger & Courteau (2015) mass-tolight transformations are consistent with other transformations such as Zhang et al (2017). Numerous uncertainty factors affect stellar mass estimates and are described in the luminosity and colour sections (Sections 3.3.2 and 3.3.4) Equation 10 expresses the stellar mass calculation.…”
Section: * [M ]mentioning
confidence: 62%
“…We choose g − z colour over g − r (which can also be measured from the DESI-LIS) for its longer baseline and low measurement error. Colours are useful as inputs to colour mass-to-light transformations (Taylor et al 2011;Conroy 2013;Roediger & Courteau 2015;Zhang et al 2017;García-Benito et al 2019) and can be used to construct scaling relations on their own. The g − z colours are calculated as:…”
Section: G − Z [Mag]mentioning
confidence: 99%
“…Indeed, galaxy star-formation histories are complex. However, it is shown that scatter in the mass-to-light ratio derived from different starformation history for a given color is ∼0.2 dex, see §4.3 Zhang et al (2017). Therefore, we consider ±0.2 dex as a typical conservative error on our stellar mass estimates.…”
Section: Data Analysis 31 Analysis Of Archival Datamentioning
confidence: 94%